Clinical Outcomes of Early Intensive Treatment of Rheumatoid Arthritis - Prapan Booranaburidej (2022)
Introduction: As learnt from previous international early arthritis cohort, early remission is the treatment target for rheumatoid arthritis. To reach that outcome, early intervention with adequate DMARDs is crucial especially in the first year of disease. Objective: We evaluate the efficacy of combination DMARDs and tight control strategy in early rheumatoid arthritis patients of Ramathibodi Hospital. Methods: Early RA patients (onset < 1 years) were enrolled to the tight control treatment protocol at Ramathibodi hospital from March 2012 to March 2013. All the patients received combination of first line DMARDs with or without low dose corticosteroids and were followed every 6 weeks for clinical assessment using disease activity score evaluating in 28 joints (DAS 28). Control group was early RA followingup at the Police General hospital at the same period. The treatment target was disease controlled at low DAS (DAS 28 < 3.2) or remission (DAS 28 < 2.6). Results: At 24 weeks, 48% of RA patients gained disease remission and 80% could be controlled in low DAS. After diseases were controlled at 12 weeks, up to 60% of patients can be maintained in low DAS until 24 weeks. While in the control group, there was only one from six patients (17%) reached remission at 24 weeks. Time to low DAS or remission was 9 weeks in the treatment group, compared with 22 weeks in the control group. However, at baseline, there were more patients in treatment group using low dose corticosteroid than in the control group (76% VS 17%, P = 0.024). Conclusion: Remission is the realistic goal in RA treatment with early combination therapy and tight control. Low dose corticosteroids increase treatment efficacy in early phase of treatment in study population.